1998
DOI: 10.1001/archfami.7.6.575
|View full text |Cite
|
Sign up to set email alerts
|

Physician Interaction With Battered Women: The Women's Perspective

Abstract: We identified discrete sets of desirable and undesirable physician behaviors. Further research is needed to clarify racial differences found in this study. Findings can help guide both clinical practice and the development of physician training curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 16 publications
5
57
0
6
Order By: Relevance
“…54 Although our participants did not ask for safety planning, in a study that surveyed 115 IPV victims who had sought help from IPV agencies, 25% reported safety planning done by a physician and considered it a desirable behavior. 55 Physicians might *Warning symptoms and conditions: injuries (ask about the mechanism of the inquiry, if mechanism does not make sense, consider probing further in a nonjudgmental manner); chronic pain (headache, abdominal pain, including irritable bowel syndrome, pelvic pain, back pain, etc); vague somatic complaints (fatigue, dizziness); mental health issues (depression, anxiety, post-traumatic stress disorder, substance abuse); abuser's inappropriate behavior in the offi ce. 5-12 † Safety assessment: evaluate suicide oe homicide risk (victim and abuser), weapons or threat to use weapons (victim and abuser), drug and alcohol use (victim and abuser), abuse of children, abuse of pets, escalating severity of abuse, threats to life.…”
Section: Intimate Partner Violence Victim Managementmentioning
confidence: 99%
“…54 Although our participants did not ask for safety planning, in a study that surveyed 115 IPV victims who had sought help from IPV agencies, 25% reported safety planning done by a physician and considered it a desirable behavior. 55 Physicians might *Warning symptoms and conditions: injuries (ask about the mechanism of the inquiry, if mechanism does not make sense, consider probing further in a nonjudgmental manner); chronic pain (headache, abdominal pain, including irritable bowel syndrome, pelvic pain, back pain, etc); vague somatic complaints (fatigue, dizziness); mental health issues (depression, anxiety, post-traumatic stress disorder, substance abuse); abuser's inappropriate behavior in the offi ce. 5-12 † Safety assessment: evaluate suicide oe homicide risk (victim and abuser), weapons or threat to use weapons (victim and abuser), drug and alcohol use (victim and abuser), abuse of children, abuse of pets, escalating severity of abuse, threats to life.…”
Section: Intimate Partner Violence Victim Managementmentioning
confidence: 99%
“…[7][8][9] Many have called for using a single question designed to detect intimate partner violence embedded within general health behavior surveys. 10 -12 "Safety" questions (eg, "Do you feel safe at home?…”
mentioning
confidence: 99%
“…Следи препрека да се жртве стиде и боје не-разумевања околине (61,0%). Наши резултати су исти као у сличним студијама 23,25,26 . Да је препрека то што се жене враћају у исто окружење сматра 53,7% испитаника, ста-тистички значајно више лекара (р=0,039), у британској студији 11% 15 .…”
Section: препреке у вези са самим жртвама насиљаunclassified
“…У великом броју студија је утврђено да већина жр-тава нема ништа против тога да буду питане о насиљу Снежана Б. Кнежевић и сар. Препреке код здравствених радника за откривање више жена жртава насиља у породици Општа медицина 2017;23(3-4):67-77 и очекују од здравствених радника да буду активнији у постављању питања, што није случај са ставом наших испитаника 25,26,30,31 . Током свакодневног рада, здравстве-ни радници треба да искористе терапеутски потенцијал и препознају насиље, да га јасно осуде, да осећају и по-казују емпатију према жртви током разговора, да пону-де континуитет у пружању здравствене заштите, да буду свесни тога да није њихов задатак решавање тог пробле-ма, већ вештина да упуте на надлежне институције 1,6,7,32 .…”
Section: препреке у вези са самим жртвама насиљаunclassified